2022
DOI: 10.1155/2022/9862733
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Network Pharmacology and Molecular Docking Integrated Surface Plasmon Resonance Technology to Investigate the Potential Targets and Mechanisms of Tripterygium wilfordii against Pulmonary Artery Hypertension

Abstract: Background. Pulmonary artery hypertension (PAH) is a rare, life-limiting cardiopulmonary disorder characterized by the progressive and remodeling of pulmonary vasculature. Although the development of the technology brings us many approaches for the treatment of PAH, the effect of treatment is unsatisfactory. Tripterygium wilfordii (TW), as a traditional Chinese medicine (TCM), has been widely used in anti-inflammation, anticancer, and other fields. However, the potential of TW in treating PAH is currently uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, molecular docking studies have demonstrated that Cordycepin can effectively bind to P53 and P21 proteins, supporting its potential mechanism of action in treating PAH (Fig. 11) 37 .…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, molecular docking studies have demonstrated that Cordycepin can effectively bind to P53 and P21 proteins, supporting its potential mechanism of action in treating PAH (Fig. 11) 37 .…”
Section: Discussionmentioning
confidence: 79%
“…[15][16][17] Likewise, researchers have tried to apply bioinformatics analysis in the study of PH to elucidate the potential functions of circRNAs related to PH, mostly based on databases and animal experiments. [18][19][20][21][22][23][24][25][26][27][28] However, few studies have utilized clinical samples diagnosed by RHC, and researches for COPD-PH are even fewer. To the best of our knowledge, the present study is the first to profile circRNA expression of lung tissues from COPD patients with mean pulmonary artery pressure (mPAP)≥20 mmHg measured by right heart catheterization (RHC).…”
Section: Introductionmentioning
confidence: 99%